Reliability of VHF telemetry data for measuring attendance patterns of marine predators: a comparison with time depth recorder data - Lowther, A D; Ahonen, H; Hofmeyr, G; Oosthuizen, W C; De Bruyn, P J N; Lydersen, C; Kovacs, K M (Marine Ecology Progress Series, 2015)
Very high frequency (VHF) radiotelemetry data has been used for over 30 yr to monitor the behavior patterns of otariid seals. These data have been used in a wide variety of ways, from characterizing the reproductive and foraging ecology of these species to inferring ecosystem changes based on variation in attendance patterns. Yet the accuracy of VHF data has never been appropriately evaluated. Our study compares VHF data collected on 16 lactating Antarctic fur seals to assess onshore attendance with concurrently collected time depth recorder (TDR) data used as the true measurement of time spent onshore. Within the retrieved datasets, 25% of the VHF data could not be interpreted with any reliability. Additionally, there were significant differences in the number and duration of attendance bouts between the 2 instrument types, with VHF data overestimating attendance bout duration by approximately 8.9 h on average. Importantly, the magnitude and direction of errors between VHF and TDR measurements were not systematic, suggesting that VHF data is an inappropriate method for collecting attendance data. Modelling the raw VHF data in a state-space framework elicited mean attendance durations that were indistinguishable from TDR-derived measurements, suggesting this approach may provide a means to re-examine historic VHF data. Moreover, given the evolution of electronic tags in terms of sophistication, miniaturization, longevity and decreasing cost over the last 30 yr, TDRs are a more appropriate means of collecting attendance data on centrally foraging marine mammals such as otariids.
Keywords: Bouvetøya; NARE ekspedisjoner; Sørishavet; marin zoologi; overvåking; pelsseler; pinnipedier; radio telemetri; økosystemer

At-sea behaviour of three krill predators breeding at Bouvetøya—Antarctic fur seals, macaroni penguins and chinstrap penguins - Blanchet, Marie-Anne; Biuw, Martin; Hofmeyr, Greg; de Bruyn, P. J. Nico; Lydersen, Christian; Kovacs, Kit M. (Marine Ecology Progress Series, 2013)
Keywords: Bouvetøya; krill; pelsseler; pingviner; pinnipedier; plankton; seler; zoologi

Intraspecific differences in the diet of Antarctic fur seals at Nyrøysa, Bouvetøya - Hofmeyr, Greg; Bester, Marthán; Kirkman, Stephen; Lydersen, Christian; Kovacs, Kit (Polar Biology, 2010)
Intraspecific differences in the diets of many species of pinnipeds are to be expected in view of the great differences in morphology, life history and foraging behaviour between the sexes of many species. We examined the diet of the Antarctic fur seal population at Bouvetoya, Southern Ocean, to assess intersexual differences. This was made possible by the analysis of prey remains extracted from scats and regurgitations collected in areas used primarily by one or the other sex. The results indicate that both males and females feed primarily on Antarctic krill Euphausia superba with several species of fish and squid being taken, likely opportunistically given their prevalence. Significant differences were identified in the frequency of occurrence of otoliths in scats and the percentage numerical abundance of the major fish prey species in the diet. Adult males ate a smaller quantity of fish overall, but ate significantly more of the larger fish species. The greater diving capabilities of males and the fact that they are not limited in the extent of their foraging area by having to return regularly to feed dependant offspring may play a role in the differences found between the diets of males and females. Additionally, females might be more selective, favouring myctophids because they are richer in energy than krill. The absence of major differences in the diet between the sexes at this location is likely due to the high overall abundance of prey at Bouvetoya.
Keywords: Bouvetøya; marin biologi; pelsseler; pinnipedier; seler; sjøpattedyr